A Influência dos hormônios sexuais no balanço entre as citocinas pró-inflamatórias e anti-inflamatórias em machos e fêmeas SHR, após o tratamento com enalapril - Dalpiaz, Polyana Lima Meireles (2011)
Introduction: Angiotensin II, a peptide formed from the action of angiotensin converting enzyme (ACE) on angiotensin I, is a primary mediator of the reninangiotensin system (RAS) and in addition to hemodynamic effects, is involved in key events the inflammatory process. The use of ACE inhibitors, apart from hemodynamic benefits, is associated with anti-inflammatory effects, however, still unclear whether ACE inhibitors have beneficial effects on the balance between pro-and anti-inflammatory cytokines and hormones can interfere with this relationship. Thus, this study was designed to investigate in SHR rats, males and females, castrated and intact, the potential benefit of ACE inhibitors on serum levels of inflammatory biomarkers, IL-10, IL-6 and TNF-α, since that these cytokines play important roles in the pathogenesis of inflammatory diseases. Objective: To evaluate the influence of gender on the effect of enalapril on serum levels of proinflammatory cytokines (IL-6 and TNF-α) and antiinflammatory (IL-10) in SHR rats. Methods: SHR, adults, both sexes, with 12 weeks, weight 150 ± 8 g (females) and 230 ± 10 g (males), were separated into eight experimental groups (n = 7) are: Males and Females 1) SHAM + Treatment with vehicle, 2) SHAM + treatment with enalapril, 3) castration + treatment with enalapril, 4) castration + treatment with vehicle. Treatment by gavage with enalapril (10mg/kg/day) was started after 21 days of castration and lasted 4 weeks. Sham group animals underwent sham surgery group and the castrated animals, underwent bilateral ovariectomy and orchidectomy, males and females respectively. We analyzed the plasma ACE activity of the cytokines IL-10, IL-6 and TNF-α. Level of significance: p <0.05. Results: Enalapril reduced SBP and ACE activity in all treated groups, we observed sexual dimorphism in plasma levels of IL-10, TNF-α and IL-6 in the sham groups, with higher values in females. The withdrawal of sex hormones made disappear the difference between males and females in relation to inflammatory cytokines and reversed the pattern of response. Enalapril treatment increased IL-10 in all treated groups, thus improving the balance proand anti-inflammatory, regardless of gender. Conclusion: The neutralization of the actions of angiotensin II by ACE inhibitors in SHR may exert anti-inflammatory and anti-hypertensives, regardless of sex, but dependent on sex hormones to reduce pro-inflammatory cytokines.